Implementation of Android-Based Salon Booking Application for Customer Service Optimization - Samudra, Tegar Bayu; Anggara, Afwan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Most beauty salons are still using manual system to manage booking and customer, which made queue long, record incorrect and customer frustrated. Purpose of this research is to create an Android based Salon booking application for IKA Salon (which fulfill operational needs) and thus increase service quality and enhance the customer satisfaction. This study is done by use of Research and Development (R&D) model which consists needs analysis followed by design development system testing. We built it using Flutter (the framework) and Firebase for real-time storage and management of data. It offers user registration, login, service scheduling(booking), customer data management etc Key findings show that application can resolve some manual problems like also queuing, scheduling improvement and recording errorless operation. Additionally, the app brings major improvements in operations and client happiness. Serving mobile service booking and management of schedule, customer data in real-time makes the application play an optimising role for a salon and help its growth of business